Implementasi Kebijakan UHC (Universal Health Coverage) Di Kota Medan - Ramadha Yanti Parinduri; Barham Siregar; Dasema Hulu (JURNAL ILMIAH EDUNOMIKA, 2023)
The implementation of the UHC (Universal Health Coverage) policy in Medan City is a government policy that supports health development for all Indonesian people. The achievement of this policy was also influenced by the large number of Medan City Health BPJS participants whose membership status was inactive, so the government thought and acted to activate the membership. However, active participants and paying regularly are also very helpful for the government to achieve cross-subsidies from the contributions paid by participants. The aim of this UHC (Universal Health Coverage) policy is to be able to protect the community in terms of health insurance with good services. In this case the author uses a qualitative approach, while for data analysis using descriptive techniques based on problems related to the role and participation of the community in the UHC (Universal Health Coverage) program and government strategies to increase the effectiveness and efficiency of the program. The results of this study indicate that in the implementation of the UHC policy in Medan City, people have the opportunity to access health services for free without any fees to be paid when illness occurs, with standard inpatient services in class 3 (three). As for service quality, it is hoped that the government will pay more attention to health facilities and routine outreach to the public.